Effects of grain-size distribution and hysteresis on soil-water characteristic curve (SWCC) - Zou, Lei (2019)
The relationship between water content and soil suction, referred to as the soil-water characteristic curve (SWCC), plays a central role in understanding the behaviour of an unsaturated soil. The SWCC is used to estimate the water coefficient of permeability, shear strength, volume change and aqueous diffusion of unsaturated soils. However, there are still gaps in the current understanding of the SWCC. This thesis investigates the effects of grain-size distribution and hysteresis on the SWCC. Pore size distribution (PSD) governs the SWCC. There is a correlation between PSD and grain size distribution (GSD). Hence, GSD has often been used to estimate SWCC. To obtain the parameters of the GSD, it is more convenient if the GSD can be described by a mathematical equation. In this study, the equations for GSD were first reviewed and an improved GSD equation was proposed and used in this study. Sigmoidal or unimodal SWCC is common. More recently, it is recognised that bimodal SWCC is present for some soils. The SWCC is usually determined by laboratory tests at discrete suction levels. If some important suction levels are not tested, the SWCC data could be wrongly interpreted as a unimodal SWCC when it should be a bimodal SWCC. A bimodal SWCC is corollary to dual porosity. Dual porosity can arise due to bimodal GSD. Bimodal SWCC can be due to bimodal GSD or soil aggregations due to reconstitution. This study only addresses bimodal GSD.. This study developed a classification tree to distinguish bimodal GSD soils with bimodal SWCC from bimodal GSD soils with unimodal SWCC. The classification tree can serve as a guide to determine the discrete suction levels in laboratory determination of SWCC so that critical suction levels are not missed from the test to avoid wrong interpretation of the SWCC. Based on the study, recommendations were made to change the suction levels proposed in the standard for determination of SWCC. It is recommended that suction levels for unimodal and bimodal SWCCs are different with bimodal SWCC having more suction levels than unimodal SWCC. The estimation of SWCC from other easily, routinely, or cheaply measured properties, such as GSD, index properties and dry density or void ratio, is performed with pedotransfer functions (PTFs). The PTFs for estimating SWCC can be divided into two types: point-estimation and parametric-estimation. A number of point-estimation PTFs has been proposed to estimate the water contents for suctions of 4(or 3), 10, 33, 100 and 1500 kPa for soils of a specific region soil. It is "expected" that the PTF will perform poorly when applied to soils of other regions. This thesis examines the relevancy and usefulness of PTFs in unsaturated soil mechanics by evaluating numerous PTFs using data collated from the literature. The data covers a wide region so that specificity bias of the PTFs is removed in the evaluation. Based on the evaluation, a simple estimation method for unimodal SWCC was proposed. The simple estimation method was demonstrated to work well. In unsaturated soil mechanics, researchers have developed one-point methods to estimate SWCC. One-point methods are actually parametric-estimation PTFs used together with one-point measurement of the SWCC. One-point methods reduce the wait time to obtain an estimate of the SWCC. However, one-point measurement of the SWCC is expensive and time-consuming. This study developed a zero experimental point method by eliminating the need of using a one-point measurement of the SWCC. The one-point measurement of SWCC is substituted using two point-estimation PTFs. The zero experimental point method was demonstrated to work as well as the one-point method but is more advantageous as no one point measurement of the SWCC is needed. It is widely recognised that the water content of a soil at a certain suction is not unique. Water content of a soil on the wetting path is always lower than on the drying path for the same suction. This is referred to as hysteresis of SWCC. The hysteretic nature of SWCCs has been known for a long time, but in many routine engineering applications the drying SWCC is often used since the measurement of a complete hysteretic SWCC is extremely time consuming and costly. Few hysteresis models have been proposed for SWCC. But these models require data on the wetting SWCC for model calibration, which increases the difficulty of applying unsaturated soils in engineering practice. In this study, a relatively simple model, which requires limited data and no data on the wetting SWCC for estimating the hysteretic SWCC is proposed. The proposed SWCC hysteresis model outperformed the other SWCC hysteresis models. Bimodal SWCCs are associated with dual-porosity soils. Determination of bimodal SWCC in the laboratory is costly and time-consuming. Few bimodal SWCC estimation parametric-estimation PTFs have been proposed but the existing bimodal SWCC estimation PTFs are very complicated. In this research, a parametric-estimation PTF was proposed to estimate bimodal SWCC and was shown to provide good agreement with experimental data from the literature. No hysteresis model has been proposed for bimodal SWCC. In this research, a model to estimate the hysteresis of bimodal SWCC was proposed based on the hysteresis model proposed for unimodal SWCC in this research. Good agreement of the estimation with experimental data was shown for the limited experimental data available in the literature.